Inspeção dos equipamentos elétricos da rede de média tensão da UFERSA Campus Caraúbas - Marinho, Hortência Cibelle da Silva (Universidade Federal Rural do Semi-Árido, 2018)
Electrical inspections are essential in installations to verify the operational state of the electrical equipment to prevent accidents due to damages in these elements, damage to equipment, occurrence of fires or electric discharge in technicians and operators. The purpose of this work is to perform the inspection and survey of the equipment installed in the UFERSA Caraúbas electricity distribution network in order to verify compliance with the electrical design and with the requirements required by the COSERN standard on power supply distribution voltage to the individual building. The work was developed in two stages. In the first stage, a verification of the electric design of the UFERSA Caraúbas electric distribution network was carried out and an on-site comparison was made with the equipment present in the installation. In a second step, a checklist was created based on the standard Electricity Supply in Medium Voltage Distribution to Individual Construction, in order to help and streamline the process of recording information regarding the equipment of the distribution network. With this, a standard of conformity between the equipment installed and the electrical design was verified, as well as with the requirements of the norm. However, some differences were observed in some transformers installed with less power available in the project, but this fact does not compromise the operation of the distribution network.
Monografia
Keywords: Inspeção; Rede de distribuição; Média tensão; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA